2017
DOI: 10.1108/ijebr-11-2015-0230
|View full text |Cite
|
Sign up to set email alerts
|

Networks and entrepreneurial learning: coping with difficulties

Abstract: Purpose-Many scholars analyse networks and learning to understand how individuals successfully create and manage new ventures. Based on the assumption that entrepreneurs learn from networks, this study examines which types of difficulties encourage entrepreneurs to use networks to facilitate learning, whether entrepreneurs change networks to deal with such difficulties, and which network characteristics facilitate learning. Design/methodology/approach-Networks are considered a potential source of learning, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 77 publications
2
57
0
7
Order By: Relevance
“…All the principals acknowledged the potential role of significant others as a means of compensating for a lack of competency in specific areas of business practice corroborating arguments by Timmons and Spinelli (2009), Rae (2007), Taylor and Thorpe (2004), Leitch et al (2013) and Soetanto (2017). This study did not however suggest that networks were more or less important at different stages of business development/growth, as concluded in previous studies, but found their overall impact on Entrepreneurial Practitioners to be significant.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…All the principals acknowledged the potential role of significant others as a means of compensating for a lack of competency in specific areas of business practice corroborating arguments by Timmons and Spinelli (2009), Rae (2007), Taylor and Thorpe (2004), Leitch et al (2013) and Soetanto (2017). This study did not however suggest that networks were more or less important at different stages of business development/growth, as concluded in previous studies, but found their overall impact on Entrepreneurial Practitioners to be significant.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, what emerges is the concept that the lone entrepreneur has been challenged, and in its place the idea of effective entrepreneurial activity being highly dependent on relationship networks both inside and outside of the businesses (Devins et al, 2002;Harding, 2004;Taylor and Thorpe, 2004;Rae, 2007). The role of the founder's network of contacts, including family and friends, as well as business contacts is crucial; core dimensions of any entrepreneurial practitioner's human capital, (Leitch et al, 2013;Soetanto, 2017). Baggen et al (2016) identify the role of 'significant peers' in providing support to entrepreneur's learning, particularly in the early stages of startup and business development, people identified as knowledgeable and experienced in business practice with a willingness to share and guide the Entrepreneurial Practitioner as he/she experiences the many challenges of starting, and subsequently developing, a business venture.…”
Section: Entrepreneurial Practitioner Learning: a Theoretical Perspecmentioning
confidence: 99%
See 1 more Smart Citation
“…chambers of commerce, Church, Rotary or Lions Club) (Davidsson and Honig, 2003). Weak ties are crucial because they represent bridges to access networks or groups of people (Soetanto, 2017). Yet, in comparison with strong ties the amount of information, support or empathy to be procured through weak ties is uncertain.…”
Section: Network and Social Relationshipsmentioning
confidence: 99%
“…Sharing bisnis bertujuan untuk memperluas jaringan bisnis. Soetanto, D. (2017) menemukan entrepreneur mampu mengembangkan jaringan, sebagian besar memiliki ikatan kuat untuk pembelajaran eksploitatif. Gambar ini merupakan hasil karya peserta.…”
Section: Gambar 4 Tahap 4 (Entrepreneur Enabler) Dari Program Pengabunclassified